Baudelaire, nature and the artist in society - Howell, Jane (Rhodes University, Faculty of Humanities, Department of Fine Art, 1980)
From Conclusion: The Artist can regard Baudelaire as a touchstone, as so many of his ideals and maxims are the ideals and maxims of the Artist himself. He teaches us many invaluable secrets of the universe and his lucid rendering of their explanations give us a clear insight into its mystery. He believed that Art was the 'brainchild' of Nature's inspiration and that through its means and ways Natures mysteries will be revealed to us. He fought against all that the modern-day Artist is stiII fighting against. He rebelled against society1s false reasoning and its false morals. He became 'self-exiled' so that he could retain his individuality and reasoning. Like the Artist, his most valuable quality was his spontaneity and inspiration, given to him when his spirit moved him. His poems stand complete in themselves and yet all have a mysterious quality binding them. Likewise our paintings must also stand complete, they must be an end in themselves, each with its own singular message and yet a unity must prevaiI throughout. We must strive for that eternal quality that is so obvious in Baudelaire1s work. He can be read today at the distance of a century as if he had written for the present generation, with a knowledge of its problems and interests. His appeal is still vital because he was not fettered by the fashionable opinions and evanescent whims of his own age, and he made no concessions to the spirit of his own time in order to gain popularity.
Keywords: Baudelaire, Charles, 1821-1867